2022
DOI: 10.3390/nu14030674
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Effects of Exercise and Physical Activity on the Gut Microbiome of Older Adults

Abstract: Recent evidence suggests that exercise/physical activity (PA) can beneficially alter the gut microbiome composition of young people, but little is known about its effects in older adults. The aim of this systematic review was to summarize results of human studies that have assessed the effects/associations of PA/exercise on the gut microbiome of older adults and to better understand whether this can help promote healthy ageing. Seven studies were included in the review and overall, exercise and increased amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 124 publications
(214 reference statements)
0
31
1
Order By: Relevance
“…Physical activity, exercise, or physical fitness are considered advantageous therapies to decrease inflammatory pathways [ 47 ]. Recent evidence proposes that exercise can positively modify the intestinal microbiota composition in healthy adults [ 47 , 48 ]. These changes can also be discovered in patients with inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity, exercise, or physical fitness are considered advantageous therapies to decrease inflammatory pathways [ 47 ]. Recent evidence proposes that exercise can positively modify the intestinal microbiota composition in healthy adults [ 47 , 48 ]. These changes can also be discovered in patients with inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…[18,19]. For several studies have pointed out that the composition of the GM of centenarians of various ethnicities and geographical positions presents a high biodiversity and representation of Firmicutes, Bifidobacterium, as well as SCFA producers, with their respective anti-inflammatory and homeostatic properties, when compared with the elderly or younger adults [20][21][22], supports the concept that gut microbiota behavior does not reflect chronological but biological aging [18].…”
Section: The Role Of the Aging Process And Exercise Training On Intes...mentioning
confidence: 73%
“…Regarding specific bacteria composition, Erlandson et al [21] found that after a 24-week of combined exercise intervention with a gradual increase in intensity in men older sedentary, there was an increase in the genera Bifidobacterium, Oscillopsira, and Anareostipes, while decrease Oribacterium and Prevotella. In a recent systematic review, it was observed that different exercise modalities (aerobic and resistance training) may act through changes in the gut environment such as rises in the production of short-chain fatty acids, bile acids alteration, lipopolysaccharide reduction, besides regulation of mucus production which may, in turn, change the composition of the gut microbiome towards a healthier one by promoting the growth of health-related bacteria, and a decrease in harmful bacteria [22].…”
Section: The Role Of the Aging Process And Exercise Training On Intes...mentioning
confidence: 99%
“…Physical exercise also increases short-chain fatty acid levels in both humans and rodents, which is beneficial for multiple organ dysfunction in sepsis ( Allen et al, 2018 ). Physical exercise enhances SCFA levels by increasing SCFA-producing bacteria, including the propionate producer Propionibacterium freudenreichii and the butyrate producers Faecalibacterium prausnitzii ( Húngaro et al, 2020 ; Ramos et al, 2022 ) . Furthermore, physical exercise increases the diversity of the gut microbiome and decreases gut transit time.…”
Section: Molecular Mechanisms Of Physical Exercise In Sepsis Treatmentmentioning
confidence: 99%